Spectrophotometric Methods for Simultaneous Estimation of Diclofenac Sodium and Rabeprazole in Combined Dosage Form - CHOUDHARY*, BALRAM; GOYAL†, ANJU; L. KHOKRA, SUKHBIR (Asian Journal of Chemistry, 2024)
Two fast, precise and economical spectrophotometric methods have been developed for the simultaneous estimation of diclofenac sodium and rabeprazole in a combined dosage form. Simultaneous determination of the marketed brands was carried out using simultaneous equation method and two wavelength calculation methods. An attempt was made to estimate both the drugs in a combined dosage form. Methanol was used as a common solvent for both the drugs. Linearity was observed at both wavelengths in the concentration range of 10-50 μg/mL for each drug. The result of analysis have been validated statistically and also by recovery studies.